Effects of vitamin D supplementation on cognitive and emotional functioning in young adults--a randomised controlled trial. - Angela J Dean (Public Library of Science (PLoS), 2011)
Background Epidemiological research links vitamin D status to various brain-related outcomes. However, few trials examine whether supplementation can improve such outcomes and none have examined effects on cognition. This study examined whether Vitamin D supplementation led to improvements in diverse measures of cognitive and emotional functioning, and hypothesised that supplementation would lead to improvements in these outcomes compared to placebo. Methods/principal findings Healthy young adults were recruited to a parallel-arm, double-blind trial conducted at The University of Queensland. Participants were randomly allocated to receive Vitamin D (one capsule daily, containing 5000 IU cholecalciferol) or identical placebo capsule for six weeks. All participants and outcome assessors were blinded to group assignment. Primary outcome measures assessed at baseline and 6 weeks were working memory, response inhibition and cognitive flexibility. Secondary outcomes were: hallucination-proneness, psychotic-like experiences, and ratings of depression, anxiety and anger. 128 participants were recruited, randomised and included in primary analyses (vitamin D n = 63; placebo n = 65). Despite significant increases in vitamin D status in the active group, no significant changes were observed in working memory (F = 1.09; p = 0.30), response inhibition (F = 0.82; p = 0.37), cognitive flexibility (F = 1.37; p = 0.24) or secondary outcomes. No serious adverse effects were reported. Conclusions Our findings indicate that vitamin D supplementation does not influence cognitive or emotional functioning in healthy young adults. Future controlled trials in targeted populations of interest are required to determine whether supplementation can improve functioning in these domains. Australian and New Zealand Clinical Trials Registry; ACTRN12610000318088.